CENSIS, OECD and a lesson from the past to counter misinformation and promote the well-being of democracy - Costantin, Maria; Benussi, Fulvio Oscar (Community Notebook. People, Education and Welfare in the Society 5.0, 2024)
Our permeability to fake news represents a real emergence, which is bound to worsen with the advent of artificial intelligence (hereafter A.I.). Democracy is at risk of being ‘hacked’ by the rapid spread of false or misleading information, often conveyed by disinformation campaigns by domestic or foreign actors that create confusion, exacerbate polarisation, distort public policy debates, deteriorate citizens’ trust in institutions and undermine the well-being of democracy.